Oh my stars - Kilpatrick, Sally (Kensington Books, 2018)
Like most things in Ellery, Tennessee, this year<U+2019>s Drive Thru Nativity is a little unconventional. The Dollar General parking lot doubles as a Bethlehem stable, and widowed writer Ivy Long, who<U+2019>s been roped into playing Mary, sure as heck isn<U+2019>t a virgin. But then comes an unexpected development: a genuine, real-life baby left in the manger, with only a brief note. And somehow, in the kerfuffle that follows, Ivy finds her life is about to change . . . The holidays are a bittersweet time for Ivy<U+2014>filled with memories of her beloved late husband and reminders that life doesn<U+2019>t always offer the happily-ever-afters her readers expect. So when Ivy ends up with custody of the baby, she can only chalk it up to a Christmas miracle. She doesn<U+2019>t know if it will be forever, but with help from family, she<U+2019>ll make little Zuzu<U+2019>s first Christmas a good one. The nativity<U+2019>s Joseph, aka Gabe Ledbetter, has a pediatrics background that<U+2019>s coming in mighty handy. In turn, Ivy is helping Gabe find his place in the quirky community. If that place turns out to be somewhere near Ivy, well, maybe this particular Christmas story will turn out to be merry and bright after all . . .